2017
DOI: 10.1021/acsami.7b06597
|View full text |Cite
|
Sign up to set email alerts
|

Development of Epigallocatechin-3-gallate-Encapsulated Nanohydroxyapatite/Mesoporous Silica for Therapeutic Management of Dentin Surface

Abstract: In dental clinic, unsatisfactory management of the dentin surface after dentin exposure often leads to the occurrence of dentin hypersensitivity and caries. Current approaches can occlude the tubules on the dentin surface to relieve dentin hypersensitivity; however, the blocked tubules are generally weak in combating daily tooth erosion and abrasion. Moreover, cariogenic bacteria, such as Streptococcus mutans, produce biofilm on the dentin surface, causing caries and compromising the tubules' sealing efficacy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 59 publications
2
55
0
Order By: Relevance
“…The HAp growth in the present study may follow a top-down mode, since we did not observe the amorphous calcium phosphate (ACP) nanoprecursors-templated apatite nucleation and growth that is an important feature for a bottom-up mode. The pure PTL nanofilm had already been proven to have good biocompatibility, [43] and the in vitro cytotoxicity of the lyso-PEG film was further investigated by the Cell Counting Kit-8 (CCK-8). [34] These reported results thus suggested that the amyloid-like lysozyme nanofilm could work as robust glue to hold a huge potential application on creating functional organic-inorganic hybrid biomaterials with excellent interfacial bonding stability.…”
Section: Wwwadvmatde Wwwadvancedsciencenewscommentioning
confidence: 99%
See 1 more Smart Citation
“…The HAp growth in the present study may follow a top-down mode, since we did not observe the amorphous calcium phosphate (ACP) nanoprecursors-templated apatite nucleation and growth that is an important feature for a bottom-up mode. The pure PTL nanofilm had already been proven to have good biocompatibility, [43] and the in vitro cytotoxicity of the lyso-PEG film was further investigated by the Cell Counting Kit-8 (CCK-8). [34] These reported results thus suggested that the amyloid-like lysozyme nanofilm could work as robust glue to hold a huge potential application on creating functional organic-inorganic hybrid biomaterials with excellent interfacial bonding stability.…”
Section: Wwwadvmatde Wwwadvancedsciencenewscommentioning
confidence: 99%
“…[41] Encouraged by the above results, we further designed in vivo animal experiments to ascertain the clinical performance of the lyso-PEG oligomers on occluding DTs in a real oral environment. The pure PTL nanofilm had already been proven to have good biocompatibility, [43] and the in vitro cytotoxicity of the lyso-PEG film was further investigated by the Cell Counting Kit-8 (CCK-8). The cell viability assay of L929 fibroblasts cells indicated negligible cytotoxicity from the lyso-PEG film (even better than that of the control group) ( Figure S25, Supporting Information).…”
Section: Doi: 101002/adma201903973mentioning
confidence: 99%
“…Calcium, potassium, and ferric oxalate have also been used to treat DH, but oxalate precipitates were removed or dissolved by saliva [27]. Nano-hydroxyapatite, which has been recently recommended for tubular occlusion, forms soluble compounds that impair its long term efficacy [34].…”
Section: Discussionmentioning
confidence: 99%
“…Huang and co‐workers prepared hydroxyapatite‐MS materials loaded with epigallocatechin‐3‐gallate for the therapeutic elimination of Streptococcus mutants biofilms . UV–visible measurements indicated that epigallocatechin‐3‐gallate was released from the material in a sustainable fashion over 96 h. Besides, MTT viability assays carried out with the nanocomposite showed nontoxicity for human dental pulp stem cells.…”
Section: Ms In Antibacterial Applicationsmentioning
confidence: 99%